Development of performance indicators for Thai autonomous university hospitals - Wipada Kunaviktikul (2018)
The purpose of this study was to develop performance indicators for a Thai autonomous university hospital. The study was comprised of two stages; Stage 1: Content validity and prioritization of performance indicator items and Stage 2: Probability of use of the performance indicators. The instruments used for data collection were a set of questionnaires. The sample included experts in autonomous organization administration, public organization administration and hospital administration. The results showed that the majority of experts agreed with the proposed performance indicator items and most of them rated those items with high priority. Thus, performance indicators can be applied directly to measure the performance of a Thai autonomous university hospital. As for those items which were rated by some experts with "moderate" or "low" priority, they can be included as indicators later as necessary. Based on the findings of this study, implications for university administration, university hospital administration, nursing administration and nursing education are suggested.